Vilken inverkan har ett stigande ränteläge på kommersiella fastighetsbolag? - Ståhl,Lukas; Tran,Phillip (2025)
For the past few years, the commercial real estate companies in Sweden have been affected by rising interest rates from previously low levels. The interest rates started to rise at the beginning of 2022, a challenging period for most of the commercial real estate companies. This can not only be seen in the companies financial data but also on the stock market. The media has written about the challenges of highly leveraged companies in the context of higher costs related to interest rates. Commercial real estate companies are usually more leveraged in comparison to other sectors, thus they are more sensitive to higher interest rates. The purpose of this work has been to explore how the real estate companies have handled the rising interest rates and what strategies they’ve had. To explore this the following question was developed. - What strategies do commercial real estate companies have to manage rising interest rates? To explore this question, a quantitative and a qualitative study have been conducted. In the quantitative study, financial data from 21 companies during 2020 to 2024, have been gathered and analyzed, such as loan- to- value, interest coverage ratio, solidity, cashflow and results. Financial data from the stock market has also been gathered to get a view of the companies performance in comparison to other sectors. The qualitative study contained interviews and correspondence with 10 different real estate companies. The interviews were anonymous and not part of the same selection as the quantitative study.
Keywords: Kommersiella fastighetsbolag; ränteläge; strategier; finansiell risk